Cultivation of Creative Thinking of Students in Interior Design Teaching - Zheng , Zhaofang (Journal of Theory and Practice of Contemporary Education, 2023)
With the improvement of material and cultural living standards, the public has higher requirements for interior design. Therefore, it is an inevitable trend to vigorously innovate the teaching mode of interior design and strengthen the innovative thinking of designers. This paper first discusses the connotation of creative thinking, then deeply analyzes the significance of cultivating creative thinking of interior design students, and puts forward practical optimization strategies.